(untitled) (Journal of Hama University, 2026)
This study aims to evaluate the effects of intravenous diazepam injection at a dose of 0.3 mg/kg on clinical and biochemical indicators in pregnant bitches and to monitor the vitality of the puppies following a cesarean section. The experiment involved eight adult female dogs from local breeds (weighing 6–8 kg; aged 2–4 years). Clinical and blood indicators were recorded before injection and at 30 and 60 minutes post-injection, while puppy vitality was assessed immediately after birth and for one hour. The results showed a significant decrease in the heart rate, respiratory rate, temperature, and maternal responsiveness at 30 and 60 minutes post-injection. Blood tests revealed a non-significant decrease in WBC, Na⁺, and K⁺, as well as a non-significant increase in liver enzymes (ALT and AST), without exceeding normal limits. The puppies exhibited initial relative lethargy, with gradual recovery in activity, respiration, and reflexes within one hour after birth. The findings suggest that intravenous DZP is relatively safe for the mothers at the administered dose, with a temporary effect on the puppies, necessitating their monitoring after birth. These results support the modern protocols for using benzodiazepines in cesarean anesthesia, with caution when handling newborn puppies.